Open Access to Electronic Theses and Dissertations: What's Right for Me - Lewis, Janice; Patterson, Belinda (East Carolina University, 2009)
Presentation made Monday, October 19, as part of Open Access Week 2009 at ECU, focusing on advantages and concerns associated with open access to electronic theses and dissertations and the history of ETDs at ECU.
Keywords: Open access; Electronic theses; Electronic dissertations; Institutional repositories